Associação entre variáveis climáticas e qualidade da água para consumo humano por meio de técnicas multivariadas - Rodrigues, Sergio Augusto [UNESP] (2015)
Several factors may contribute for changing water quality parameters, especially climate variables. Knowning that water is a natural paramount resource for human activities, researches observing its rational and sustainable use are crucial. Intended for human consumption, water must have physical, chemical and microbiological characteristics up to harmless levels to health which are determined by public health agencies as well as characterized by its potability standards. This research observed physicochemical and microbiological characteristics which are important for monitoring water quality analysed through daily collected samples at randomized sections within water distribution network and also at the final water treatment sector in Botucatu, SP, Brazil, from 2007 to 2011. Among physical and chemical variables it was observed residual chlorine, pH, turbidity, apparent color, fluorine and water temperature. While on microbiological characteristics it was observed total coliforms occurrence and the number of heterotrophic bacteria colony forming units. This paper aims at evaluating simultaneously treated water characteristics and distribuition in Botucatu, SP, Brazil with a set of climate variables. Multivariate data analysis technique was used aiming to develop and improve the quality of information as well as an unusual methodological procedure in the areas involved. Results showed the association between specific climate situations and some water quality characteristics.